Impact of Cry1Ab toxin expression on the non‐target insects dwelling on maize plants. (5th September 2012) - Habuštová, O.; Doležal, P.; Spitzer, L.; Svobodová, Z.; Hussein, H.; Sehnal, F.
Abstract The effect of transgenic maize MON810 (Bt maize) on the diversity and abundance of plant‐dwelling insects was tested under field conditions in southern Bohemia (coordinates 48°N, 14ºE, 384 m a.s.l.) for three successive years. The experiment was carried out on 10 0.5‐ha plots of which five were seeded with the Bt maize and five with the non–Bt parental cultivar. The content of Bt toxin (Cry1Ab) was measured in plant tissues with a commercial ELISA kit. Randomly chosen plants (10 per plot) were taken from the field during the vegetation period in about 2‐week intervals and thoroughly examined in the laboratory. Collected insects were identified and their counts were statistically analysed with CANOCO with respect to the Bt toxin, developmental stage of maize and the year of cultivation. No significant effect of Bt maize on the plant‐dwelling non‐target insects was detected. Correlation between the number of plants and detected insect diversity revealed that inspection of 20 plants (four per each of five plots) provided data reliable at 95% probability level; six plants per plot were sufficient for the analysis of aphids, thrips and Orius bugs.